Novel, acidic, and cold-adapted glycoside hydrolase family 8 endo-β-1,4-glucanase from an Antarctic lichen-associated bacterium, Lichenicola cladoniae PAMC 26568 - Kim, Do Young; Kim, Jonghoon; Lee, Yung Mi; Byeon, Soo Min; Gwak, Jeong Hae; Lee, Jong Suk; Shin, Dong-Ha; Park, Ho-Yong (Frontiers in Microbiology, 2022)
Endo-β-1,4-glucanase is a crucial glycoside hydrolase (GH) involved in the decomposition of cellulosic materials. In this study, to discover a novel cold-adapted β-1,4-D-glucan-degrading enzyme, the gene coding for an extracellular endo-β-1,4-glucanase (GluL) from Lichenicola cladoniae PAMC 26568, an Antarctic lichen (Cladonia borealis)-associated bacterium, was identified and recombinantly expressed in Escherichia coli BL21. The GluL gene (1044-bp) encoded a non-modular polypeptide consisting of a single catalytic GH8 domain, which shared the highest sequence identity of 55% with that of an uncharacterized protein from Gluconacetobacter takamatsuzukensis (WP_182950054). The recombinant endo-β-1,4-glucanase (rGluL: 38.0 kDa) most efficiently degraded sodium carboxymethylcellulose (CMC) at pH 4.0 and 45oC, and showed approximately 23% of its maximum degradation activity even at 3oC. The biocatalytic activity of rGluL was noticeably enhanced by >1.3-fold in the presence of 1 mM Mn2+ or NaCl at concentrations between 0.1 and 0.5 M, whereas the enzyme was considerably downregulated by 1 mM Hg2+ and Fe2+ together with 5 mM N-bromosuccinimide and 0.5% sodium dodecyl sulfate. rGluL is a true endo-β-1,4-glucanase, which could preferentially decompose D-cellooligosaccharides consisting of 3 to 6 D-glucose, CMC, and barley β-glucan, without other additional glycoside hydrolase activities. The specific activity (15.1 U mg-1) and kcat/Km value (6.35 mg-1 s-1 mL) of rGluL toward barley β-glucan were approximately 1.8- and 2.2-fold higher, respectively, compared to its specific activity (8.3 U mg-1) and kcat/Km value (2.83 mg-1 s-1 mL) toward CMC. The enzymatic hydrolysis of CMC, D-cellotetraose, and D-cellohexaose yielded primarily D-cellobiose, accompanied by D-glucose, D-cellotriose, and D-cellotetraose. However, the cleavage of D-cellopentaose by rGluL resulted in the production of only D-cellobiose and D-cellotriose. The findings of the present study imply that rGluL is a novel, acidic, and cold-adapted GH8 endo-β-1,4-glucanase with high specific activity, which can be exploited as a promising candidate in low-temperature processes including textile and food processes.